KONFLIK NORMATIF UU MINERBA DENGAN OTONOMI DAERAH PASCA 2020: ANALISIS KOMPARATIF DAN MODEL KEWENANGAN KOLABORATIF - Muhammad Hatta; Ummi Hafsah Nur Anisa; Yusnita Yusnita; Hanifah Dhyaul Haq (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2026)
The centralization of Mining Business License (IUP) issuance authority following Law Number 3 of 2020 and Law Number 11 of 2020 concerning Job Creation has created significant normative conflict with the principle of regional autonomy guaranteed under Article 18 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia. This research analyzes the normative disharmony between the 2020 Mining Law, the Job Creation Law, and the Regional Government Law, as well as its impact on procedural justice in mining governance. Employing normative legal research methodology with statutory, conceptual, and comparative approaches, this study compares mining licensing systems in three countries: Kazakhstan (post-Soviet centralization with transparency reforms), Germany (coordinative federalism with mandatory public participation), and India (federalism with judicial activism). The findings reveal that Indonesia's extreme centralization lacks precedent in the mining licensing systems of developed countries and contradicts global best practices. Kazakhstan demonstrates that centralization can coexist with transparency when supported by digitalization. Germany illustrates the effectiveness of coordinative federalism with mandatory public participation. India exemplifies the strategic role of the judiciary in enforcing indigenous communities' rights through the Free, Prior and Informed Consent (FPIC) principle. This research recommends a collaborative authority model that proportionally integrates central, provincial, and local government authorities, strengthened community participation through FPIC, transparent digital licensing systems, and enhanced judicial oversight through Constitutional Court review of sectoral regulations. Keywords: Normative Conflict, Regional Autonomy, Mining Business License, Comparative Legal Study, Procedural Justice